A novel fiber-fretting test for tribological characterization of the fiber/matrix interface. (1st February 2021) - Kabel, Joey; Edwards, Thomas E.J.; Hain, Caroline; Kochetkova, Tatiana; Parkison, Darren; Michler, Johann; Hosemann, Peter
Abstract: Ceramic matrix composites exhibit excellent high temperature properties and are candidate materials for structural applications from jet engines to nuclear fuel cladding. The strength and deformation behavior of these composites are intrinsically tied to the properties of the fiber/matrix interface. This research introduces a novel technique to evaluate the fundamental friction and wear characteristics of these interfaces. A case study on SiCf /PyC/SiCm composites applies in situ fiber fretting to investigate the kinetic friction coefficient and cyclic wear characteristics of the interphase. The experimental methodology is presented in explicit detail to encourage other researchers to explore the capabilities of this technique. Testing was carried out as a function of fiber roughness, PyC thickness (≈10, 500, 1200 nm), cycle count (10, 100, 1000), and frequency (1, 5, and 10 Hz). The friction coefficient and wear behavior changed with cycle length due to a transition from adhesive to abrasive mechanisms. SEM fractography provided insights to tribological evolution from adhesive sliding to three-body abrasive wear. The structural disorder at the tribo-surface relating to graphitic content and dangling bond density was investigated using Raman spectroscopy. Properties are contextualized with comparison to uniaxial tensile behavior of the parent composite. Highlights: Novel technique for friction and wear characterization of fiber/matrix interfaces. User defined stress, cycle length, and frequency explore friction dependencies. Access to the tribo-surface enables Raman and other surface characterizations. Adhesive and abrasive wear regimes are observed depending on interphase structure.